Bioinspired multilevel interconnected networks with porous multiwalled nanotubes built by heterogeneous nanocrystallites. Issue 1 (2nd August 2019) - Chen, Shikun; Yang, Chengzhi; Wu, Lingling; Su, Huilan; Zhu, Yifu; Li, Guoyao; Song, Fang; Zhang, Wang; Gu, Jiajun; Liu, Qinglei
Abstract: Inspired by fiber‐interwoven eggshell membrane (ESM) with associated specific permeability and transport performance, interconnected nanotube networks are constructed to empolder relevant distinctive properties and functional advantages. In this work, a typical ESM‐templated procedure combined with stepwise impregnation and gradient calcination is developed to accomplish the fabrication of multilevel frameworks from TiO2 nanocrystallites to porous multiwalled nanotubes (NTs) to final interconnected networks. During the impregnation process, in situ mineralization occurs on ESM fiber substrate to generate Ti‐impregnant coating with variant composition and layered structure. Followed by the calcination, anatase TiO2 porous NTs come into being as ESM templates decompose at 500°C, then heterogeneous nanocrystallites are achieved at higher temperature. Thus, the final ESM‐morphic nanocomposites present interconnected networks woven by porous multiwalled NTs. Benefiting from interconnected multichannels of multilevel networks and controllable heterogeneous nanocrystallites, the ESM‐inspired TiO2 would behave higher light‐excitation and transport efficiency, which can achieve more valuable applications such as photocatalytic degradation to some organic pollutants. Abstract : Porous multiwalled nanotube networks constructed by heterogeneous nanocrystallites provide interconnected multichannels, which can achieve high transport efficiency as well as unique 1D electrochemical properties.